2018
DOI: 10.1007/s12012-018-9444-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intralipid Emulsion in the Rat Model of Digoxin Intoxication

Abstract: Although the mechanism of action is not well known, intravenous lipid emulsion (ILE) has been shown to be effective in the treatment of lipophilic drug intoxications. It is thought that, ILE probably separates the lipophilic drugs from target tissue by creating a lipid-rich compartment in the plasma. The second theory is that ILE provides energy to myocardium with high-dose free fatty acids activating the voltage-gated calcium channels in the myocytes. In this study, effects of ILE treatment on digoxin overdos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Besides, we observed toxic effects of ILE on the kidney cells in the 2 nd group which we had administered only ILE. Even if the underlying mechanism is not fully understood studies showing that ILE itself is renal toxic, our findings are also consistent with the literature (31,32). Some experimental studies also showed that pioglitazone also has toxic effects on heart tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, we observed toxic effects of ILE on the kidney cells in the 2 nd group which we had administered only ILE. Even if the underlying mechanism is not fully understood studies showing that ILE itself is renal toxic, our findings are also consistent with the literature (31,32). Some experimental studies also showed that pioglitazone also has toxic effects on heart tissue.…”
Section: Discussionsupporting
confidence: 92%
“…20 Ml Ampul for Infusion, İlaçsan ® /Turkey), ILE (ClinOleic 20% lipid 500 mL, ECZACIBAŞI Baxter/Belgium), and 0.9% NaCl were administered with an infusion pump (Swiss Made, Arcomed AG Volumed VP 7000, Kloten, Switzerland). The medication dosages and administration methods were determined and the experimental protocol was designed based on the study reports in the literature and references explained previously [8,13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Dosages, drug application methods and experimental protocols were determined according to the previous studies and the mentioned sources [8,13,14].…”
Section: Experiments Protocol and Groupsmentioning
confidence: 99%